Simulation and Optimization of Hybrid Energy Systems for Green Hydrogen Production in Industrial Settings - Arianto, Supri; Rahayu, Yeni Sri; Suwarno, Suwarno (Journal of Mechanical Engineering, Science, and Innovation, 2025)
The global push toward Net Zero Emissions (NZE) has positioned green hydrogen as a key component in sustainable energy strategies. In Indonesia, the energy sector contributes over 40% of national emissions, prompting the need for increased renewable energy integration. However, green hydrogen production remains limited due to high costs and dependency on fossil-based electricity. This study focuses on a hydrogen production facility located in the Gresik industrial port area, which currently relies 91% on electricity from the national grid. To address this, we propose a hybrid energy system combining photovoltaic (PV) and grid power. The goal is to reduce the Levelized Cost of Energy (LCOE) while increasing the share of renewable energy in hydrogen production.A simulation-based approach was used, employing HOMER Pro software with real industrial operational data as input. Several scenarios were developed by varying PV capacity and daily load demand. The optimal configuration consisting of a 6.179 MWp PV system and a 5,000 kWh/day load resulted in the lowest LCOE of IDR 2,175/kWh, compared to the baseline of IDR 2,783/kWh. The renewable energy share also increased from 9% to 21%.Additionally, performance analysis showed that the actual PV system efficiency was 21%, slightly lower than its theoretical efficiency due to seasonal weather variations. These results indicate that higher PV integration and larger energy loads significantly improve both cost-effectiveness and renewable energy penetration.This study demonstrates a practical, data-driven approach for optimizing green hydrogen production systems in industrial environments.